2-mercaptoethane sulfonate (MESNA) protects against burn-induced renal injury in rats - YEGEN, BERRAK; ŞENER, GÖKSEL (ELSEVIER SCI LTD, 2004)
Animal models of thermal injury implicate oxygen radicals as causative agents in local wound response and distant organ injury following burn. In this study we investigated the putative protective effects of 2-mercaptoethane sulfonate (MESNA) against oxidative kidney damage in rats with thermal injury. Under ether anaesthesia, shaved dorsum of the rats was exposed to 90 degreesC bath for 10 s to induce burn injury. Rats were decapitated either 6 or 24 h after burn injury. MESNA was administered i.p. immediately after burn injury. MESNA injections were repeated once more 12 h after the first injection in the 24 h burn group. In the control group the same protocol was applied except that the dorsum was dipped in a 25 degreesC water bath for 10 s. Kidney tissues were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, protein oxidation (PO), myeloperoxidase (MPO) activity and collagen contents. Creatinine, urea concentrations (BUN) and lactate dehydrogenase (LDH) in blood were measured for the evaluation of renal functions and tissue damage, respectively. Tissues were also examined microscopically. Severe skin scald injury (30% of total body surface area) caused significant decrease in GSH level, significant increase in MDA level, protein oxidation (PO), MPO activity and collagen content of renal tissue. Serum creatinine was slightly increased at the early phase of thermal trauma but not changed in 24 h groups. On the other hand BUN and LDH were significantly elevated by thermal trauma in both 6 and 24 h of burn groups. Treatment of rats with MESNA significantly increased the GSH level and decreased the MDA level, PO, MPO activity, collagen contents, BUN and LDH. Since MESNA reversed the oxidant responses seen in burn injury, it seems likely that MESNA could protect against thermal trauma-induced renal damage. (C) 2004 Elsevier Ltd and ISBI. All rights reserved.
Keywords: MESNA; burn; lipid peroxidation; glutathione; THERMAL-INJURY; LIPID-PEROXIDATION; ANTIOXIDANT THERAPY; N-ACETYLCYSTEINE; FREE-RADICALS; MODEL; INFLAMMATION; PRODUCTS; MYELOPEROXIDASE; GLUTATHIONE